The global impact of COVID-19 on infertility services. Issue 2 (2020) - Ory, Steven J.; Miller, Kathleen A.; Horton, Marcos; Giudice, Linda
Abstract : The COVID-19 pandemic has posed unique concerns and potential risks to women now pregnant or considering childbearing. Although no professional societies have issued recommendations that women avoid conception at this time, several professional organizations recommended a moratorium on infertility services including both medically assisted reproduction and assisted reproductive technology shortly after the World Health Organization declared COVID-19 infection to be a pandemic. Reasons cited for undertaking these extraordinary measures included prevention of possible complications of assisted reproductive technology and medically assisted reproduction and virus induced complications of pregnancy including potential vertical transmission to the fetus and optimization use of critical health care resources. A survey of reproductive health providers in 97 countries was undertaken to assess their response to the pandemic and recently issued guidance. Although different countries reacted differently with diverse responses and variable resources, the results suggest that the reproductive health community has largely been responsive to public health and individual patient concerns.